Role of nano-additives in the thermal management of lithium-ion batteries: A review. (April 2022) - Kumar, Rajan; Mitra, Abhijeet; Srinivas, Tangellapalli
Highlights: Different BTMSs are discussed in brief The comprehensive analysis of nanofluid-based BTMS is carried out The comprehensive analysis of nano-enhanced PCM-based BTMS is carried out An in-depth analysis of the effect of nanoparticle concentration in base fluid and PCM on the performance of BTMS is presented This review paper also discusses the future scope of work to boost the cooling efficiency of BTMS Abstract: Concerns about the safety of Lithium-ion batteries (LIBs) due to undesirable thermal behavior highlight the importance of an effective thermal management strategy to prevent thermal runaway. Consequently, it is essential to choose the best approach for LIBs to maintain a reasonable range of cell temperatures. Due to the low thermal conductivities of liquid or phase change materials (PCM), liquid cooling/ phase change materials-based battery thermal management systems (BTMSs) are incapable of keeping battery temperatures within safe limits at higher charging or discharging rates. Nanotechnology has already shown enormous success in many fields. This review paper offers a comprehensive assessment of the use of nanomaterial in fluids and PCMs to augment the thermal conductivity of the fluids and PCMs and thus enhances the performance of the BTMS. The thermal management strategies that are widely used nowadays are nanofluid cooling based-BTMS and nano-enhanced PCM based-BTMS. This paper provides a review based on previous studies summarizing the thermal performance of the nano-enhanced PCM and nanofluid cooling based-BTMS of LIBs. The maximum temperature rise, temperature difference, and percentage lessening in maximum battery temperature rise or temperature difference are the metrics used to assess the BTMS's performance. Moreover, the effect of various parameters, including discharge rate, flow channel configuration, coolant inlet velocity, mass, and thickness of PCM, and the concentration of nano-additives on the thermal performance of LIBs is extensively examined. This review paper also discusses the future scope of work to boost the thermal efficiency and heat dissipation rate of BTMS to attain the highest performance of the battery packs while using less energy and carrying less weight. It is anticipated that this paper will offer greater insights into the fundamentals and perceptions of the nano-enhanced PCM and nanofluid cooling based-BTMSs of LIBs, leading to the augmentation of the thermal performance of BTMS integrated with nano-enhanced PCM and nanofluid.